Zealandia, Our Continent Revealed - Berridge, Mike (New Zealand Science Review, 2015)
​Zealandia is not yet a household name in New Zealand or worldwide, but if Nick Mortimer and Hamish Campbell had their way, the tattered and anachronistic New Zealand flag would metamorphose into a new emblem that boasts the reality of Zealandia and this flag would flap from our flagpoles. Additionally, Zealandia would become a defining component in our national anthem, also due for a refresh, to use current political vernacular. The last time I spoke with Hamish he was headed northwest on a mission to better define the far-reaching but poorly prospected underwater boundaries of Zealandia, claimed to be the world’s 7th continent. Norfolk Island, Lord Howe Island, and New Caledonia notwithstanding, the flag may need a little remodelling to reflect political and colonial realities of distant territorial islands swallowed up by Zealandia, but these holes in the fabric and its raggy edges would have their own unique charm, and would not detract much from the expansive geological reality of Zealandia, 94% of it below water. The book is engaging and scientifically compelling and has been lovingly written and superbly illustrated for the intelligent layperson with an interest in things geological.